Proximal Dissection and Rupture of a Popliteal Cyst: A Case Report. (10th October 2012) - Abdelrahman, M. H.; Tubeishat, S.; Hammoudeh, M.
Abstract : Popliteal cysts are swellings in the popliteal fossa due to enlargement of the gastrocnemius semimembranous bursa. These cysts might burst, and they usually rupture posteriorly and inferiorly with severe pain in the calf. We describe a patient with popliteal cyst that dissected proximally and ruptured in the soft tissue of the thigh.